DISEÑO, CONSTRUCCIÓN Y PRUEBAS EXPERIMENTALES PRELIMINARES DE UNA COCINA DE VAPOR SOLAR - Espinoza Paredes, Rafael (1999)
The Renewable Energy Center from the Universidad Nacional de Ingeniería (CER-UNI) develops and promotes research in the field of non conventional and renewable energy resources technologies (ER&NC). Food cooking with solar energy and solar cookers has been going on for 30 years now. And in the last years we have seen an unusual interest in the matter in many countries in the world including Perú. This is the reason why solar cooking models of many characteristics have been promoted. The solar cooker that is part of this work is called Solar Steam Cooker (CVS) because of the physical phenomenon produced that generates cooking. In fact, by a Compound Parabolic Concentrator (solar collector), the steam generated goes to a cooking container through pipers, here, the steam surrounds it completely transferring the heat to the food that is in it. Results on tests made in the Laboratory of Heat and Hydraulic Machines at the Mechanical Engineering School (UNI), in a prototype with a cooking quantity of 4 liters approximately, have been very encouraging to continue and demonstrate the technical and economic feasibility of this machine.